ANALISIS KEMAMPUAN PEMAHAMAN MATEMATIS PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL - Deliska Takalao; Vivian E. Regar; Murni Sulistyaningsih (ADIBA : JOURNAL OF EDUCATION, 2022)
The ability of students' mathematical understanding of the system of linear equations of two variables in Class VIII of SMP Negeri 5 Manado is very diverse, and there needs to be a special review of this. The purpose of this study was to determine the students' mathematical understanding ability based on the level of ability category on the material of the two-variable Linaer equation system. The subjects in this study, namely several students of class VIII SMPN 5 Manado, who will be selected based on a test to determine their level of ability 2 students with moderate ability, and 2 students with low ability with the total number of subjects selected is 6 students. The results of this study showed that there were 4 students in the high ability category, 7 students in the medium ability, and 9 students in the low ability category.